Analysis of the current situation in the field of electronic services in Syrian banks and prospects for their development - E. V. Vasilieva; A. Alhannash (Управление)
The study is aimed at determining the level of electronic services provided in Syrian banks and identifying the level of their compliance with the trends of modern technological developments. The authors make the comparison of the Syrian banks with the best practices of using information technologies to provide their services by world banks that use the concept of electronic service.The study showed, that despite the banking sector in Syria is striving to be modern and improve along with technological developments, there is a significant reduction in the use of electronic banking. Syrian banks are required to adhere to a sufficient number of material and technical requirements to implement the concept of a real electronic service. Among the priority tasks the authors highlight the expansion of the use of electronic money in the country, the network of ATM machines, bank cards. However, in order to reach the level of global banks, it is important to move to a digital omnichannel development strategy.As an example of the implementation of ecosystem projects, the paper considers some of leading Russian companies that build their ecosystem around customers based on the principle of “Lifestyle Banking”. Based on Russian practice, the article presents a number of recommendations that will improve the electronic banking of Syria. This will allow the country not only to restore the banking system, but also give the opportunity to keep up with global technological advances, as well as compete with international banks.